COVID-19 IN PREGNANT WOMEN AND THEIR NEWBORNS : A REVIEW - Rina Puspita (Excellent Midwifery Journal, 2020)
The outbreak of the Coronavirus disease 2019 (COVID-19) in China in December 2019 is a pandemic all over the world. COVID-19 raised concerns about the possibility of vertical transmission of the virus from mother to fetus. This literature review aims to explore the available knowledge of presents current studies about developing COVID-19 in pregnant women and their newborns also review clinical features of neonates born to mothers with COVID-19, vertical transmission of  COVID-19 from infected pregnant mothers to neonates, breasfeeding during the COVID-19, the risk of COVID-19 may increase preterm birth. COVID-19 in children is characterized by fever and cough, where fever and cough are the most common symptoms. Poor prognosis is very rare in COVID-19 in children. However, as this virus is spreading globally and becoming a global pandemic, it should not be ignored that its incidence will increase in pregnant women and high-risk groups. This review provides an important picture for further studies of COVID-19 infection in children.Keywords: COVID-19, Pandemic, Mother, Newborn, Neonates, Breastfeeding, Transmission, Vertical.